Selection of the most suitable refrigerant for a shell and tube condenser - Dalkilic, A. S.; Mahian, O.; Wongwises, S. (SPRINGER, 2014)
A theoretical performance study on a shell and tube condenser with various refrigerant blends was conducted for various ratios proposed by other researchers in the literature. The theoretical results showed that all of the alternative refrigerants investigated in the analysis have a slightly lower convective heat transfer coefficient than their base refrigerants. The refrigerant mixture of R290/R600, R152a/R125/R32 and R32/R134a were found to be the most proper replacement refrigerant among the alternatives.
Keywords: PRESSURE-DROP CHARACTERISTICS; EVAPORATION HEAT-TRANSFER; CO2/DME MIXTURE REFRIGERANT; HORIZONTAL SMOOTH TUBE; DOMESTIC REFRIGERATORS; HYDROCARBON MIXTURES; TRANSFER COEFFICIENTS; R-290 PROPANE; R-600 BUTANE; PERFORMANCE; Thermodynamics; Mechanics